2(2n+9)=4(n+13)

Simple and best practice solution for 2(2n+9)=4(n+13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2n+9)=4(n+13) equation:



2(2n+9)=4(n+13)
We move all terms to the left:
2(2n+9)-(4(n+13))=0
We multiply parentheses
4n-(4(n+13))+18=0
We calculate terms in parentheses: -(4(n+13)), so:
4(n+13)
We multiply parentheses
4n+52
Back to the equation:
-(4n+52)
We get rid of parentheses
4n-4n-52+18=0
We add all the numbers together, and all the variables
-34!=0
There is no solution for this equation

See similar equations:

| -14+31-6=m | | 2y2(11/8y)=190 | | 120=-4/15x-24 | | 2x+7=5x-2=1=18 | | 20y-12y-5y=18 | | 21-3+8=m | | 6p-1+7p=14 | | y+16=55 | | 5/4n+2=17 | | 2+5-2x=-14 | | 6x-4+10x=2(7x-3) | | 8.7=35x-2.5(5.4-6x) | | j-34=57 | | c=4.5(14) | | 10(0.4b-0.2)=0.25(8b+16) | | 9(x-1/12=3(x+3/8 | | 14=0.432x−10.44 | | 4+2(x+2)=-10 | | t^+2t=6 | | 4x+8=8x+4=14x-10 | | -6=p-1+2 | | 16x−15−9x=13 | | c=49+14 | | 4(x-3)/6=2(x+5)/11 | | 2.19=z/2 | | 6(x-3)-7=-25 | | (24x+4)^-1=0 | | 3/5x-2=2x-7 | | 4x+16=-2(2x-5)+6 | | 4i/i=4/1•i/i=4/1 | | -7(1-2n)=-105 | | |x|+18=4 |

Equations solver categories